COVID-19 response in low- and middle-income countries: Don’t overlook the role of mobile phone communication (2020)
Estimates of health capacities in the context of the coronavirus disease 2019 (COVID-19) pandemic indicate that most low- and middle-income countries (LMICs) are not operationally ready to manage this health emergency. Motivated by worldwide successes in other infectious disease epidemics and our experience in Sub-Saharan Africa, we support mobile phone communication to improve data collection and reporting, communication between healthcare workers, public health institutions, and patients, and the implementation of disease tracking and subsequent risk-stratified isolation measures. Programmatic action is needed for centrally coordinated reporting and communication systems facilitating mobile phones in crisis management plans for addressing the COVID-19 pandemic in LMICs. We summarize examples of worldwide mobile phone technology initiatives that have enhanced patient care and public health outcomes in previous epidemics and the current COVID-19 pandemic. In addition, we provide an overview of baseline conditions, including transparency about privacy guarantees, necessary for the successful use of mobile phones in assisting in the fight against COVID-19 spread.